Pemanfaatan Tanaman Obat Keluarga (TOGA) sebagai Upaya Peningkatan Kesehatan Mandiri Masyarakat Desa Purwodadi - Munthe, Salman; Triana Purba, Devi; Hasibuan, Nazmi Atika; Aritonang, John Agus Winata; Ginting, Oddy Alfonsius (Maslahah: Jurnal Pengabdian Masyarakat, 2025)
The purpose of this activity is to build a TOGA garden together with others, plant various medicinal plants that are easy to care for, and use the results for daily light treatment. The implementation method includes steps to prepare seeds and planting media, plant the plants simultaneously in the demonstration area and household yards, and monitor the care of the plants until they are ready for harvest. Ginger, turmeric, lemongrass, betel leaves, kencur, and ginger are some of the types of TOGA planted. The results of the activity showed the planting of TOGA in the yards of 25 participating families. For minor illnesses such as coughs, colds, and stomachaches, people can harvest the plants. In addition, this activity raised people's awareness of the importance of maintaining health naturally and independently. The result is that the TOGA garden will be a practical solution to support the self-reliant health of the people of Purwodadi Village and utilize the yard land productively.